2016
DOI: 10.1371/journal.pone.0157895
|View full text |Cite
|
Sign up to set email alerts
|

The Eukaryotic-Specific ISD11 Is a Complex-Orphan Protein with Ability to Bind the Prokaryotic IscS

Abstract: The eukaryotic protein Isd11 is a chaperone that binds and stabilizes the central component of the essential metabolic pathway responsible for formation of iron-sulfur clusters in mitochondria, the desulfurase Nfs1. Little is known about the exact role of Isd11. Here, we show that human Isd11 (ISD11) is a helical protein which exists in solution as an equilibrium between monomer, dimeric and tetrameric species when in the absence of human Nfs1 (NFS1). We also show that, surprisingly, recombinant ISD11 expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 43 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…S8) and extensive buried surface area (2,351 Å 2 for E. coli IscS) (37,42). The first NFS1-ISD11 interface in the SDA ec complex would not exclude a bacterial-like dimer, possibly explaining the recent discovery that ISD11 can interact but not influence the activity of bacterial IscS (43). However, the second NFS1-ISD11 interface in the SDA ec complex is not compatible with the IscS dimer.…”
Section: Resultsmentioning
confidence: 99%
“…S8) and extensive buried surface area (2,351 Å 2 for E. coli IscS) (37,42). The first NFS1-ISD11 interface in the SDA ec complex would not exclude a bacterial-like dimer, possibly explaining the recent discovery that ISD11 can interact but not influence the activity of bacterial IscS (43). However, the second NFS1-ISD11 interface in the SDA ec complex is not compatible with the IscS dimer.…”
Section: Resultsmentioning
confidence: 99%
“…In yeast (Saccharomyces cerevisiae), humans (Homo sapiens), and Trypanosoma brucei, thirteen LYRM proteins have been identified with a range of diverse roles (Table 1; Angerer, 2013). LYRM proteins were classified following the characterization of LYRM4, or ISD11, a protein involved in the stability of the Cys desulfarase (NFS1) Fe-S biogenesis complex in the mitochondrial matrix (Pfam database classification https://pfam.xfam.org/clan/CL0491; Lim et al, 2013;Yan et al, 2016;Boniecki et al, 2017). LYRM4/ISD11 mutations in a human patient resulted in CI, CII, and CIII deficiencies (Lim et al, 2013), most likely due to the fact that many subunits of the respiratory chain require Fe-S cluster insertion.…”
mentioning
confidence: 99%
“…More surprising is that Ct‐frataxin binds to the desulfurase IscS from E. coli . This is not entirely new: thanks to the high level of sequence conservation, it is possible to mix proteins from different organisms and observe interactions even though with lower affinity than for proteins from the same organism . Mixing experiments of E. coli and H. sapiens proteins had previously demonstrated that frataxins and the scaffold protein are interchangeable among species whereas desulfurases are not .…”
Section: Discussionmentioning
confidence: 99%